Microbial electrochemical recovery of zinc. (10th September 2017) - Modin, Oskar; Fuad, Nafis; Rauch, Sebastien
Graphical abstract: Highlights: Metallic Zn was electrochemically recovered from dilute Zn 2+ solutions. The lowest energy consumption for microbial electrolysis was 0.59 kWh/kg Zn. The applied voltage was 0.75 V. Operational strategies were discussed. Abstract: Electrolytic recovery of zinc (Zn) from aqueous solutions is an energy intensive process carried out using highly concentrated Zn 2+ solutions. To reduce the energy consumption and make Zn recovery possible from dilute waste streams, a more energy-efficient process is needed. In this study, we tested a microbial electrolysis cells for Zn recovery from acidic solutions. The reactors contained biological anodes that generated current by oxidizing acetate. The reactors were operated with either controlled anode potential or controlled cathode potential. During operation with controlled anode operation, the energy efficiency for Zn recovery was highly variable and depended on the biologically generated current and the Zn 2+ concentration in the catholyte. During operation with controlled cathode potential, a relatively stable energy consumption of 0.59–0.72 kWh kg −1  Zn was obtained. This was about three times lower than the energy consumption for Zn recovery under abiotic conditions.